Clinical value of chest computerized tomography scans in patients admitted with pneumonia. Issue 7 (27th March 2014) - Garg, Deepak; Johnson, Leonard B.; Szpunar, Susan; Fishbain, Joel T.
<x xml:space="preserve">Abstract</x> Patients admitted with pneumonia often receive a chest computed tomography (CT) scan for a variety of reasons. We conducted this study to evaluate our overall utilization and the clinical impact of CT scans in patients admitted to our institution with pneumonia. Patients admitted to our facility from January 2008 through November 2011 with a confirmed diagnosis of pneumonia were eligible for evaluation. Information related to patient demographics, performance of a CT scan, pneumonia‐related procedures, severity of illness, and outcomes was collected. One hundred ninety‐five patients met inclusion criteria. Sixty‐nine patients had CT scans performed. CT scans were performed more often in younger patients (58.1 ± 19.0 vs 66.8 ± 18.6, P = 0.002), individuals with lower CURB 65 (Confusion, Urea, Respiratory rate, Blood pressure, Age > 65) scores (1.7 ± 1.4 vs 2.2 ± 1.4, P = 0.037), and those with no infiltrates or consolidation on plain radiographs (26.9% vs 7.1%, P < 0.0001). Patients who had a procedure performed had longer average length of stays (15.3 ± 11.9 vs 6.8 ± 4.1 days, P = 0.016). Pneumonia‐related procedures were more likely performed in patients who had a CT scan. Specific guidelines and objective rules need to be developed to prospectively guide the use of advanced imaging techniques in pneumonia patients. Journal of Hospital Medicine 2014;9:447–450. © 2014 Society of Hospital Medicine